2019
DOI: 10.1038/s41598-019-45953-y
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin enhances human preemptive strike in both males and females

Abstract: The neuropeptide arginine vasopressin (AVP), which is known to modulate a wide range of social behaviors in animals, has been identified as a modulator of various negative responses to social stimuli in humans. However, behavioral evidence directly supporting its involvement in human defensive aggression has been rare. We investigated the effect of intranasal AVP on defensive aggression in a laboratory experiment, using an incentivized economic game called the “preemptive strike game” (PSG). Participants playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The reason why we could only detect a weak effect might be because of the relatively smaller baseline of attacking in comparison to those outlined in the previous studies (e.g., Halevy, 2017;Jind et al, 2017;Mifune et al, 2016, Simunovic et al, 2013. However, the rate of attack in this study was similar to those reported in several works (e.g., Kawada et al, 2019;Mifune et al, 2017). The diversity of experimental settings in these studies, such as stake sizes, experimental interface (i.e., laboratory or online), samples (i.e., university students or MTurk), sample sizes, and experimental manipulations, may have generated differences in the attack rate.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The reason why we could only detect a weak effect might be because of the relatively smaller baseline of attacking in comparison to those outlined in the previous studies (e.g., Halevy, 2017;Jind et al, 2017;Mifune et al, 2016, Simunovic et al, 2013. However, the rate of attack in this study was similar to those reported in several works (e.g., Kawada et al, 2019;Mifune et al, 2017). The diversity of experimental settings in these studies, such as stake sizes, experimental interface (i.e., laboratory or online), samples (i.e., university students or MTurk), sample sizes, and experimental manipulations, may have generated differences in the attack rate.…”
Section: Discussionsupporting
confidence: 77%
“…Participants might retroactively specify the reason behind their action as the action they had already performed. Third, as described in the introduction, previous studies have consistently provided empirical evidence that attacking in the PSG occurs as fear-based defensive aggression rather than an offensive one (Halevy, 2017;Kawada et al, 2019;Simunovic et al, 2013). For instance, Simunovic et al (2013) compared the rate of attack in the PSG between a condition wherein both players had an option to attack (i.e., "bilateral condition") and another wherein only one could attack their opponent unilaterally (i.e., "unilateral condition").…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations